Application prospect of AI technology in the land subsidence analysis - Tongchun QIN; Tongyun YU; Yong WANG; Di NING; Haigang WANG (Shuiwen dizhi gongcheng dizhi)
As a global geo-environmental issue, land subsidence poses a severe challenge to urban safety and sustainable development. Traditional methods for land subsidence analysis face challenges in terms of speed and accuracy in big data processing and monitoring; it thus requires new approaches. Artificial intelligence (AI) technology, as a representative of new quality productive forces, offers advantages in data preprocessing, model construction, and trend forecasting. This paper aims to further integrate AI into the study of land subsidence through a literature review. Initially, the paper provided a background introduction to AI and analyzed its current application in the field of land subsidence. The application of AI in land subsidence from the perspectives of monitoring and early warning systems, as well as macroscopic and microscopic mechanism studies was then prospected, highlighting the potential of AI in improving efficiency and accuracy. Finally, this review analyzed the limitations of AI and proposed suggestions in the future. It states that the study on land subsidence requires further assistance from AI technology. A deeper integration of AI technology into land subsidence analysis will not only improve data processing capabilities but also provide new insights into the early warning and effective control of land subsidence, contributing to the advancement and development of the field of land subsidence.